2005
DOI: 10.1007/s00702-005-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Norharman-induced motoric impairment in mice: neurodegeneration and glial activation in substantia nigra

Abstract: The beta-carboline norharman is present in cooked food and tobacco smoke and show structural resemblance to the neurotoxicant 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine. C57BL/6 mice were injected subcutaneously with norharman (3 and 10 mg/kg) twice per day for five consecutive days. Eighteen hours after the last dose an increased expression of glial fibrillary acidic protein and fluoro-jade staining were demonstrated whereas the number of tyrosine hydroxylase positive cells were unchanged in the substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Although there is some suggestion that some β‐carbolines can be neurotoxic (Haghdoost‐Yazdi, Hosseini, Faraji, Nahid, & Jahanihashemi, ; Ostergren, Fredriksson, & Brittebo, ; Ostergren, Lindquist, & Brittebo, ), evidence suggests that harmine is, if anything, neuroprotective with antiinflammatory and antiapoptotic activity (Liu et al, ; Zhong, Tao, & Yang, ) that could be beneficial in the chronic treatment of PD. In addition, these results in the MPTP‐treated primate provide support for the reports of the benefits of B. caapi and harmine monotherapy as a mild symptomatic treatment for early PD (Sanchez‐Ramos, ; Serrano‐Duenas et al, , ), as there was little or no evidence to show that there was any additive or synergistic action in conjunction with L‐DOPA that is indicated for mid to late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some suggestion that some β‐carbolines can be neurotoxic (Haghdoost‐Yazdi, Hosseini, Faraji, Nahid, & Jahanihashemi, ; Ostergren, Fredriksson, & Brittebo, ; Ostergren, Lindquist, & Brittebo, ), evidence suggests that harmine is, if anything, neuroprotective with antiinflammatory and antiapoptotic activity (Liu et al, ; Zhong, Tao, & Yang, ) that could be beneficial in the chronic treatment of PD. In addition, these results in the MPTP‐treated primate provide support for the reports of the benefits of B. caapi and harmine monotherapy as a mild symptomatic treatment for early PD (Sanchez‐Ramos, ; Serrano‐Duenas et al, , ), as there was little or no evidence to show that there was any additive or synergistic action in conjunction with L‐DOPA that is indicated for mid to late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the involvement of cholinergic, dopaminergic and serotonergic systems in β-carbolines, such as HA -induced amnesia in the step-down passive avoidance test [49,53]. Furthermore, learning and memory may be impaired due to the major effects of β-carbolines on inhibition of MAOA and MAOB [54], and the elevated level of dopamine in the synaptic clefs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that CREB can be activated by phosphorylation via several protein kinases, inter alia PKA or C, which allows the recruitment of the CREB binding protein CREBBP [88][89][90]. When primary dopaminergic cultures were treated concomitantly with 9-me-BC and the PKA/C inhibitor AG18 (tyrphostin), the stimulation of dopaminergic neurons was completely inhibited, implying an important [19] 2,9-dimethyl-b-carboline CH 3 H CH 3 H Neurotoxic effects [21], activation of microglia [22] 9-methyl-b-carboline H H CH 3 H Neurostimulation, neuroprotection and neuroregeneration of dopaminergic neurons, anti-inflammatory effects [22],…”
Section: Reviewmentioning
confidence: 97%
“…BCs, especially methylated forms such as 2,9-dimethyl-b-carbolinium ion (2,9-dime-BC + ), have been shown to exert neurotoxic effects on dopaminergic neurons [20]. They decreased dopamine uptake, induced apoptosis via increased caspase 3 levels, inhibited mitochondrial complex I, enhanced formation of ROS and activated glia and microglia [21][22][23][24]. Furthermore, harman and norharman inhibited the topoisomerase in cell nuclei and thus disturbed the DNA repair after UV-or chemical-induced DNA damage [25].…”
Section: Review Polanski Reichmann and Gillementioning
confidence: 99%